Yearbook of the United Nations 1971 - Nations Unies (United Nations, 1971)
The Yearbook of the United Nations stands as the authoritative reference work on the activities and concerns of the Organization. Based on official UN documents, the Yearbook provides comprehensive coverage of political and security matters, human rights issues, economic and social questions, legal issues, and institutional, administrative and budgetary matters.